Bilinguism in Quebec Business - Chartier, Roger (Relations industrielles / Industrial Relations, 1968)
The author defines in general terms, to the English-speaking businessman, the complex concepts and problems of language as an essential part and vehicle of culture, the relationship of language to nationalism, and the insertion of bilingualism in the business organization of today, especially in Québec.